Impact of climate change on agricultural productivity and food security in the Himalayas: A case study in Nepal. (May 2019) - Bocchiola, D.; Brunetti, L.; Soncini, A.; Polinelli, F.; Gianinetto, M.
Abstract: The paradigmatic Dudh Koshi basin laid at the toe of Mt. Everest is largely visited by tourists every year, and yet agricultural productivity and food security therein are at stake under climate change. Agricultural yield in the area recently decreased, and the question arose whether cropping at higher altitudes may help adaptation. We investigated here the present, and future (until 2100) patterns of productivity of three main rain-fed crops in the catchment (wheat Triticum L., rice Oryza L ., and maize Zea Mais L. ). We explored food security using a nutritional index, given by the ratio of the caloric content from our target cereals, to daily caloric demand. We preliminary investigated whether vertical extension of the cropped area may increase food security. We did so by (i) mapping crops area using remote sensing, (ii) setting up the agronomic model Poly-Crop, (iii) feeding Poly-Crop with downscaled outputs from global climate models, and (iv) projecting vertical land occupation for cropping, population projections, and nutritional requirements. We estimated crop yield and food security at half century (2040–2050), and end of century (2090–2100), against a control run decade CR (2003−2013), under constant land use, and projected land occupation. On average, specific wheat yield would decrease against CR by −25% (rice −42%, maize −46%) at 2100, with largely yearly variability for unchanged land use scenario. Under modified land use scenario, wheat yield would decrease by −38%, while rice and maize yield would improve, maize very slightly (−22%, and −45%, against CR) in response to occupation of higher altitudes than now. Our food security index would decrease under all scenarios (111% in 2010, 49% on average at 2050, under a population peak, and 51% at 2100), and become more variable, however with potential for adaptation by colonization of higher lands (75%, 62%, at 2050, 2100). Very large expansion of one cereal (i.e. maize), may make food security more unstable, as mostly depending on erratic yield of that cereal only. Graphical abstract: Unlabelled Image Highlights: We investigated here food security in Dudh Koshi basin under climate change. Yield of wheat, rice, and maize would decrease until the end of the century. Use of a caloric index also shows potential decrease of food security under all scenarios. Potential for adaptation is given by crop lifting upward, pending topographic constraints. Large expansion of a single crop (maize) may make food security more unstable.